Pengaruh Waktu Pemakaian Alat Kontrasepsi Suntik 3 Bulan dengan Perubahan Berat Badan pada Ibu di Klinik Abi Ummi Dw Sarmadi Palembang Tahun 2022 - Ratna Dewi; Umi Solekah; Cucu Fitrotin (KOLONI, 2022)
Injectable contraception is contraception in the form of a liquid containing the hormone progesterone which is injected into a woman's body periodically (1 month or 3 months). Weight gain due to the influence of hormonal contraception ranges from 1-5 kg ​​in the first year. The cause of weight gain is the hormone progesterone which can stimulate the appetite control center so that there is an increase in appetite and the hormone estrogen increases the speed of gluconeogenesis so that it can increase glucose levels in the blood, if glucose is not used it will be stored back in the form of fat. The more lipids are formed, the energy reserves in adipose tissue will increase, usually found in the upper arms, hips, thighs, abdomen and chest, if not balanced with a healthy lifestyle such as regular exercise and proper diet so that an increase in body weight is not controlled (obesity). The aim of the study was to determine the effect of the duration of using 3 months of injectable birth control on changes in the mother's weight. The study used an analytic survey method with a cross sectional approach. The total sampling research sample is 46 respondents. The results of the study obtained an average length of time to use KB injections of 3 months, a minimum score of 10 and a maximum of 36 was obtained, with a mean of 19.56, a median of 19 and an SD of 5.21 and an increase in body weight obtained a minimum score of 1 and a maximum of 4, with a mean of 1.86. , Median 2 and SD 0.86. The results of the linear regression test found that the p value was 0.00, which means that there was an effect of the duration of using 3 months of injection contraception on weight gain. It is hoped that counseling can be carried out about types of contraception and their side effects to mothers so that they can choose the right contraception Keywords: 3 months injectable contraception, body weight